Hubungan Toleransi Ambiguitas dengan Orientasi Kewirausahaan pada Mahasiswa Wirausaha Universitas Brawijaya Malang - Tri Wahyu Fitrianti; Tutut Chusniyah (Universitas Negeri Malang, 2021)
The purpose of this study is (1) To describe entrepreneurial orientation to the members of Entrepreneurship Students of Brawijaya University Malang (2) To describe ambiguity tolerance on several members of Entrepreneurship Students of Brawijaya University Malang (3) To between ambiguity tolerance with entrepreneurial orientation on the members Entrepreneurship Students of Brawijaya University Malang. This research used descriptive and correlational design with the sample of 88, using purposive sampling. The results of this study indicate that (1) most of the student’s ambiguity tolerance, more of have levels low, more of the students have levels of high (2) most of the student’s entrepreneurial orientation, more of have levels low, more of the students have levels of high (3) there is a negative and significant correlation between ambiguity tolerance and entrepreneur orientation. Penelitian ini bertujuan untuk (1) mengetahui gambaran toleransi ambiguitas pada anggota Mahasiswa Wirausaha Universitas Brawijaya Malang, (2) mengetahui gambaran orientasi kewirausahaan pada anggota Mahasiswa Wirausaha Universitas Brawijaya Malang, (3) mengetahui hubungan toleransi ambiguitas dengan orientasi kewirausahaan pada anggota Mahasiswa Wirausaha Universitas Brawijaya Malang. Sampel dalam penelitian ini sebanyak 88. Uji hipotesis menggunakan teknik analisis korelasi Pearson Product Moment. Hasil penelitian ini menunjukkan bahwa (1) toleransi ambiguitas pada Mahasiswa Wirausaha Universitas Brawijawa Malang menunjukkan lebih banyak masuk klasifikasi yang rendah daripada yang tinggi, (2) orientasi kewirausahaan pada Mahasiswa Wirausaha Universitas Brawijawa Malang menunjukkan lebih banyak masuk klasifikasi yang rendah daripada yang tinggi, (3) Tidak ada hubungan antara toleransi ambiguitas dengan orientasi kewirausahaan pada Mahasiswa Wirausaha Universitas Brawijaya Malang.